Supercapacitor by using different size of activated carbon from Palm Oil Kernel (PKS) as EDLC electrode - Nurdik, Mohd Ruzaleh; Nor Azmi, Nor Faranaz Shamin; Abdul Rahman, Nurul Jannah; Lepit, Ajis (Academica Press Solutions, 2023)
The large oil palm plantation in Malaysia is located in Sabah which is around 700,000 acres of land that produces around 0.7 million tons of agricultural waste. The conversion of agriculture waste to activated carbon (AC) solves the disposal problem in the agricultural industry. The AC plays an important role as an electrode in supercapacitor due to its characteristics such as high porosity and good conductivity. The performance of supercapacitor electrodes was study by using different sizes of AC. The AC from oil palm kernel shell (PKS) was produced by using the low cost of production with a simple modification in a conventional method. The PKS carbonizes in a furnace at 390 oC for 1 hour. It soaks in KOH for chemical activation. The sample is rushed by using agate mortar to get two different sizes which is fine and coarse. The AC is then mixed for the preparation of the electrode labelled as (Sample 1, Sample 2 & Sample 3). Then, the electrode is assembled with filter paper as separator and 1.0 M KOH as electrolyte. The supercapacitor electrode is connected to the circuit to observe the potential of charge-discharge. The result of capacitance for Sample 1 is 26.3mF, specific capacitance 21.58mF/g and energy density 17.22Wh/kg while the Sample 2 of activated carbon is 2672.38mF, 1113.49 mF/g and energy density 52.384Wh/kg and Sample 3 is 2952.5mF, specific capacitance 1230.16mF/g and energy density 226.34Wh/kg. As conclusion, a high-performance capacitor is achieved by using a mixed size of PKS as active material in electrode. Therefore, PKS has large market potential due to the low-cost AC production but promises high performance in Supercapacitor Application.